Preparation and characterization of methylammonium tin iodide layers as photovoltaic absorbers. Issue 4 (18th November 2015) - Weiss, Manuel; Horn, Jonas; Richter, Christoph; Schlettwein, Derck
Abstract : The preparation of absorber layers composed of methylammonium tin iodide (CH3 NH3 SnI3 ) in a two‐step process was investigated. This material is designed as a less toxic alternative to CH3 NH3 PbI3 which is commonly used as active material in perovskite solar cells. Tin(II) iodide (SnI2 ) layers prepared by physical vapor deposition were converted to CH3 NH3 SnI3 by reaction with a spin‐coated solution of methylammonium iodide (MAI). The perovskite particles formed in this process were over 200 nm in size and reached full surface coverage. A band gap of 1.23 eV was determined and the material, thus, absorbs over a broad part of the solar spectrum, broader even than CH3 NH3 PbI3 . The chemical composition and solid state structure of the prepared films were analyzed by X‐ray photoelectron spectroscopy and X‐ray diffraction, respectively. The films turned out to be remarkably stable, another key prerequisite for applications as absorber layers in perovskite solar cells. Abstract : Organic metal halides provide absorber layers for solar cells, which may not only revolutionize the fundamental view on solution‐processed semiconductor materials but also the feasibility of sustainable large‐scale photovoltaics. Presently the chemical instability of these materials and the toxicity of predominantly used lead hinder commercialization. Replacement of lead and preparation of chemically more stable materials may represent a significant step towards a technical realization of perovskite solar cells.